DEVELOPING STUDENTS’ ABILITIES IN LEARNING FOREIGN LANGUAGES - Amirkulov Asliddin Shukhratovich (Bright Mind Publishing, 2025)
This article explores the development of students’ foreign language learning abilities. It highlights key factors influencing language acquisition such as motivation, individual characteristics, interactive teaching methods, and modern educational technologies. The study emphasizes the role of innovative and communicative approaches in enhancing foreign language competence and illustrates how multimedia resources can facilitate effective learning. Furthermore, pedagogical and psychological foundations of language teaching are analyzed, and practical recommendations are provided for improving language instruction in higher education.
Keywords: Foreign language, language learning ability, students, competence, motivation, interactive methods, innovative technologies.